Overexpression and Suppression of Artemisia annua 4-Hydroxy-3-Methylbut-2-enyl Diphosphate Reductase 1 Gene (AaHDR1) Differentially Regulate Artemisinin and Terpenoid Biosynthesis - Ma, Dongming; Li, Gui; Zhu, Yue; Xie, De-Yu (Frontiers in Plant Science, 2017)
4-hydroxy-3-methylbut-2-enyl diphosphate reductase (HDR) catalyzes the last step of the 2-C-methyl-D-erythritol 4- phosphate (MEP) pathway to synthesize isopentenyl pyrophosphate (IPP) and dimethylallyl diphosphate (DMAPP). To date, little is known regarding effects of an increase or a decrease of a HDR expression on terpenoid and other metabolite profiles in plants. In our study, an Artemisia annua HDR cDNA (namely AaHDR1) was cloned from leaves. Expression profiling showed it was highly expressed in leaves, roots, stems, and flowers with different levels. Green florescence protein fusion and confocal microscope analyses showed that AaHDR1 was localized in chloroplasts. The overexpression of AaHDR1 increased contents of artemisinin, arteannuin B and other sesquiterpenes, and multiple monoterpenes. By contrast, the suppression of AaHDR1 by anti-sense of led to opposite results. In addition, an untargeted metabolic profiling showed that the overexpression and suppression altered non-polar metabolite profiles. In conclusion, the overexpression and suppression of AaHDR1 protein level in plastids differentially affect artemisinin and other terpenoid biosynthesis, and alter non-polar metabolite profiles of A. annua. Particularly, its overexpression leading to the increase of artemisinin production is informative to future metabolic engineering of this antimalarial medicine.